1999
DOI: 10.1161/01.cir.99.10.1355
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Serum Cholesterol and Hypercholesterolemic Atherosclerosis in Rabbits by Secoisolariciresinol Diglucoside Isolated From Flaxseed

Abstract: Background-Secoisolariciresinol diglucoside (SDG) is a plant lignan isolated from flaxseed. Lignans are plateletactivating factor-receptor antagonists that would inhibit the production of oxygen radicals by polymorphonuclear leukocytes. SDG is an antioxidant. Antioxidants studied thus far are known to reduce hypercholesterolemic atherosclerosis. The objective of this study was to determine the effect of SDG on various blood lipid and aortic tissue oxidative stress parameters and on the development of atheroscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
197
5
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 262 publications
(231 citation statements)
references
References 29 publications
24
197
5
5
Order By: Relevance
“…We also observed a significant increased in the plasma MDA level which serves as the marker of lipid peroxidation in these category patients. This finding is similar to the study of Prasad and Kalra; 25 they reported an increased in the blood MDA concentration in rabbits with a high cholesterol diet. We also observed a direct correlation between plasma concentration of MDA and plasma concentration of triglyceride, total cholesterol, LDLcholesterol, systolic BP and diastolic BP and on the other hand an inverse correlation with HDL cholesterol and HDL-Chol/TC ratios in both sexes.…”
Section: Discussionsupporting
confidence: 92%
“…We also observed a significant increased in the plasma MDA level which serves as the marker of lipid peroxidation in these category patients. This finding is similar to the study of Prasad and Kalra; 25 they reported an increased in the blood MDA concentration in rabbits with a high cholesterol diet. We also observed a direct correlation between plasma concentration of MDA and plasma concentration of triglyceride, total cholesterol, LDLcholesterol, systolic BP and diastolic BP and on the other hand an inverse correlation with HDL cholesterol and HDL-Chol/TC ratios in both sexes.…”
Section: Discussionsupporting
confidence: 92%
“…Hypercholesterolemic atherosclerosis is associated with an increase in the level of the lipid peroxidation product malondialdehyde, which is an index of the level of oxygen free radicals (34,35). A decrease in lipid per oxidation leads to a reduction in arterial wall choles terol content.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence suggests that there could be increased OR production contributing to the genesis of atherosclerosis. (Prasad, 1998;Kapoor and Prasad, 1996;Babior, 1984;Baynes, 1991 (Fantone and Ward, 1982;McCord and Fridovich, 1973;McCord, 1985). Moreover, the ubiquitous flavin cytosolic enzyme xanthine oxidase catalyzes the formation of superoxide anions from hypoxanthine and oxygen (Babior et al 1973).…”
Section: Oxygen Radicals and Atherosclerosismentioning
confidence: 99%
“…Reactive oxygen species have been demonstrated in growth signaling pathways and in smooth muscle cell proliferation (Colavitti et al 2002;Abe and Berk, 1999;Bhunia et al 1997). Reactive oxygen species have been suggested in the development of hypercholesterolemic atherosclerosis Prasad, 1999;Prasad, 2005;Prasad, 1997b;Prasad, 1998). Antioxidants attenuate/ prevent the development of atherosclerosis in cholesterol-fed rabbits and in humans Prasad, 1999;Prasad, 2005;Prasad, 1997a).…”
Section: Hypothesismentioning
confidence: 99%